2007
DOI: 10.1097/sle.0b013e318058a117
|View full text |Cite
|
Sign up to set email alerts
|

Choice of Approach for Appendicectomy: A Meta-analysis of Open Versus Laparoscopic Appendicectomy

Abstract: Although laparoscopic appendicectomy has been performed since 1983, the optimal approach for appendicectomy is still under debate. A systematic review and meta-analysis of all randomized controlled trials between 1995 and 2006 was undertaken. Studies were analyzed overall and in 2 subgroups (pre-2000 and post-2000) to examine for changes in outcomes with increased laparoscopic experience. Operation time was significantly longer for laparoscopy and hospital stay was shorter. Operating time reduced markedly for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
103
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(113 citation statements)
references
References 37 publications
8
103
0
2
Order By: Relevance
“…A recent meta-analysis has reported that the likelihood of intra-abdominal abscess was higher in OA as compared to LA (22). In our study, symptomatic intra-abdominal collection developed in 2 patients (6.5%) in the LA group, and they were both treated with percutaneous drainage.…”
Section: Discussionmentioning
confidence: 52%
“…A recent meta-analysis has reported that the likelihood of intra-abdominal abscess was higher in OA as compared to LA (22). In our study, symptomatic intra-abdominal collection developed in 2 patients (6.5%) in the LA group, and they were both treated with percutaneous drainage.…”
Section: Discussionmentioning
confidence: 52%
“…It is also gaining popularity because of shorter operative time, less postoperative pain, and lesser incidence of surgical site infection [8][9][10][11][12][13][14]. Its only drawback is slightly higher rate of intra-abdominal abscess [15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…У метааналізі, що об'єднав рандомізо-вані клінічні дослідження 1995-2006 рр., проведе-ному J. Bennett та співавт. (2007), було наведено дані, що ІАА при ЛАЕ розвивається в 2,26 раза частіше [15]. Водночас останнім часом у літерату-рі відмічено тенденцію до значного зниження цьо-го показника, навіть до повної відсутності різниці при ЛАЕ і ВАЕ.…”
Section: з досвіду роботиunclassified